Pembekalan Explainer Video bagi Siswa dalam Menghadapi Era Revolusi Industri 4.0 - Handoko Handoko; Angela Angela; Gunawan Gunawan (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2021)
Abstract: The 4.0 Industrial Revolution is marked by rapid advances and technological changes in various fields, including education. To welcome the era of the 4.0 Industrial Revolution, learning curriculum in schools must follow the technological advancement. Teachers generally provide group assignments to be presented by students. The main obstacle faced is that students are less capable to create and deliver presentation content. Therefore, it is necessary to provide insight about presentation ability and the use of technology to make presentations. The activity began by compiling a training module on using Explaindio Video Creator to make explainer video. Training is provided in the form of tutorials and workshops, so students can directly practice the material being discussed. Before and after the training, pre-test and post-test was conducted to test the students' understanding of the presentation using an explainer video. The results found that the average participants before attending this training did not understand the presentation technique and did not know about the presentation assisted by explainer video. After attending the training, the average participants have already understood the presentation techniques and already known about the presentation assisted by explainer video and made it on their own.           Keywords: explainer video; industrial revolution; presentationAbstrak: Revolusi Industri 4.0 ditandai dengan kemajuan dan perubahan teknologi yang pesat di berbagai bidang, tidak terkecuali bidang pendidikan. Untuk menyongsong era Revolusi Industri 4.0, kurikulum pembelajaran di sekolah harus mengikuti kemajuan teknologi. Guru mata pelajaran umumnya memberikan tugas kelompok untuk dipresentasikan oleh siswa-siswi. Kendala utama yang dihadapi adalah siswa-siswi kurang mampu membuat dan menyampaikan konten presentasi. Karena itu, perlu adanya pemberian wawasan terkait kemampuan presentasi dan pemanfaatan teknologi untuk melakukan presentasi. Kegiatan dimulai dengan menyusun modul pelatihan mengenai penggunaan Explaindio Video Creator untuk mengembangkan explainer video. Pelatihan diberikan dalam bentuk tutorial dan workshop, sehingga siswa-siswi bisa mempraktikkan secara langsung materi yang dibahas. Sebelum dan sesudah pelatihan, dilakukan pre-test dan post-test untuk menguji pemahaman siswa-siswi terkait presentasi dengan menggunakan explainer video. Hasilnya ditemukan bahwa rata-rata peserta sebelum mengikuti pelatihan ini belum memahami tentang teknik presentasi serta belum mengetahui tentang bantuan presentasi dengan menggunakan explainer video. Setelah mengikuti pelatihan, rata-rata peserta sudah dapat memahami tentang teknik presentasi serta sudah mengetahui tentang bantuan presentasi dengan menggunakan explainer video dan sudah dapat membuatnya.Kata kunci: explainer video; presentasi; revolusi industri